2015
DOI: 10.1039/c4nr05153j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nano-bowls with a Janus template

Abstract: Colloidal particles with two or more different surface properties (Janus particles) are of interest in catalysis, biological imaging, and drug delivery. Eccentric nanoparticles are a type of Janus particle consisting of a shell that envelops the majority of a core particle, leaving a portion of the core surface exposed. Previous work to synthesize eccentric nanoparticles from silica and polystyrene have only used microemulsion techniques. In contrast we report the solgel synthesis of eccentric Janus nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…8,11,12,25−29 Recently, we used a sol−gel method to form a composite particle consisting of a silica shell partially encapsulating a carboxylated polystyrene (cPS) core. 30 This morphology has also been demonstrated in Janus particles with gold 6 and iron oxide 7 cores. The common factor in all of these Janus particles is the presence of the carboxylate surface.…”
Section: ■ Introductionmentioning
confidence: 83%
“…8,11,12,25−29 Recently, we used a sol−gel method to form a composite particle consisting of a silica shell partially encapsulating a carboxylated polystyrene (cPS) core. 30 This morphology has also been demonstrated in Janus particles with gold 6 and iron oxide 7 cores. The common factor in all of these Janus particles is the presence of the carboxylate surface.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Nanobowls are a class of novel asymmetric structures. , The bowl-shaped architecture with hollow interiors and openings on their surface possess a large surface area, which render their favorable applications in catalysis, supercapacitors, and drug delivery . A number of synthetic strategies toward bowl-shaped structures have been developed, such as the self-assembly from amphiphilic block copolymers, aggregation from molecular motor induced by solvent mixing, and synergy supramolecular forces between the side chains of polymers .…”
Section: Introductionmentioning
confidence: 99%
“…The coatings are separated spatially in well-defined manners, allowing both components to interact with the surrounding environment. For example, Lal and co-workers fabricated a dumbbell-like structure composed of polystyrene and silica and used it as a template for preparing silica nanobowls . Minko and co-workers applied biodegradable dumbbell-structured nanoparticles for local pulmonary delivery of hydrophilic and hydrophobic molecules to the lungs .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lal and co-workers fabricated a dumbbell-like structure composed of polystyrene and silica and used it as a template for preparing silica nanobowls. 6 Minko and co-workers applied biodegradable dumbbell-structured nanoparticles for local pulmonary delivery of hydrophilic and hydrophobic molecules to the lungs. 7 Glaser and co-workers demonstrated that dumbbellstructured nanoparticles composed of gold and iron oxide can reduce the interfacial tension at the oil/water interface significantly.…”
Section: Introductionmentioning
confidence: 99%